Analisis Pengaruh Pemanfaatan Marketplace Ecomerce Terhadap Kinerja Penjualan Produk Lokal - Thoharudin, Kayis; Afifah, Luthfiana; Kusumastuti, Anggit Dyah (Innovative: Journal Of Social Science Research, 2024)
The developments in technology and information that have occurred have had the impact of changes, one of which is in marketing strategies which can provide business opportunities for business actors, one of which is local brands. This research aims to analyze the influence of ecommerce on sales of local products. The research method used is literature review. One of the local brands that has changed its marketing strategy is Aerostreet, which is a local shoe manufacturer at affordable prices that can be enjoyed by all groups. The results of offline sales carried out by Aerostreet were less than optimal, this is what encouraged Aerostreet to market its products online via the Shopee platform, this made the sales volume of Aerostreet shoes increase accompanied by an optimal strategy. Not only sold domestically but also abroad.